Encyclopedia of Black studies - Asante, Molefi Kete, 1942-; Mazama, Ama, 1961- (Gale virtual reference library., 2005)
Encyclopedia containing a full analysis of the economic, political, sociological, historical, literary, and philosophical issues related to Americans of African descent.